Pedagogies of pace: Temporal insights into Canadian pre-service teachers' pedagogical decision-making. (2018) - Mitton-Kükner, Jennifer; Murray-Orr, Anne
Highlights: Time epistemologies reveal PSTs' understanding of student learning. Time epistemologies identify PSTs' effective planning and pedagogical behaviors. Time epistemologies pinpoint PSTs' ability to scaffold learning. Perceptions of time influence PSTs' knowledge of planning and pedagogy. Abstract: Many suggest modern life is accelerating and attribute such perceptions to advances in technology and the commodification of clock time, as evident in how mobile technologies blur the lines between personal and professional life. As teacher educators of elementary and secondary literacies, our interest in time and its relationship to pedagogy, was in response to inductive analysis of several years of data in which pre-service teachers described time-related issues/facets related to their ability and willingness, if any, to integrate literacy into their content area teaching. This article identifies indicators demonstrating a range of pedagogical content knowledge growth in pre-service teachers as viewed through their understanding, and use of time, in relation to instructional decision-making, planning, and classroom experiences regarding the use of literacy strategies. Using time as a theoretical lens to understand pre-service teachers' developing pedagogy, we argue, suggests possibilities for how concepts of time may complement, and expand, pedagogical content knowledge scholarship.